Effectiveness of Ace Inhibitors Compared to Angiotensin Receptor Blockers on Albuminuria and EGFR Decline in Hypertensive Patients with Chronic Kidney Disease: A Systematic Review - Ni Made Dwitya Arianingtyas; Ni Wayan Sri Wardani (CV. Syntax Corporation Indonesia, 2026)
Hypertension is a major cause and complication in chronic kidney disease (CKD), with ACE inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) both being used to lower albuminuria/proteinuria and slow the progression of decreased kidney function. However, direct comparison evidence between the two still shows mixed results. This study aims to assess the effectiveness of ACEI compared to ARB on the reduction of albuminuria (primary outcome) and the decrease in eGFR/renal function (secondary outcome) in hypertensive patients with CKD through a systematic review without meta-analysis. A literature search was conducted in the PubMed database up to 15 December 2025, yielding 118 articles, which were then filtered into 5 articles for full-text assessment, with 4 studies eventually included. The studies evaluated consisted of one randomised controlled trial (RCT) and three observational studies (retrospective or prospective non-randomised). The results showed that in albuminuria/proteinuria outcomes, some studies showed a comparable effect between ACEI and ARB, while in certain subgroups, ARBs were more effective in lowering proteinuria. In kidney function outcomes, some studies reported a difference in time to serum creatinine doubling, while others found no significant difference. The risk assessment of bias suggests that most of the evidence comes from non-randomised studies with a high risk of bias, and randomised controlled trials have a moderate risk of bias. Existing evidence suggests that the effects of ACEIs and ARBs on albuminuria and renal function in hypertensive patients with CKD are varied, with the need for further research with a more robust design.